Effect of Pilates exercise on balance and spinal curvature in subjects withupper cross syndrome: a randomized controlled clinical trial - Karkousha, Rania N.; Yousef, Jermeen E.; Abdel Raoof, Neveen A.; Omran Grase, Mariam (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. To investigate the outcomes of Pilates exercise compared to traditional treatment for the management of uppercross syndrome (UCS).Methods. Forty female participants with UCS were randomly divided into two equal groups: group A (control group) andgroup B (experimental group). Both groups received two sessions per week for four consecutive weeks. Group A receiveda traditional physical therapy program consisting of stretching, strengthening, and postural correction exercises, while group Breceived a Pilates exercise program. Primary outcome measures were balance, spinal curvature, craniovertebral (CV) angle, androunded shoulders, while the Neck Disability Index and Visual Analogue Scale served as secondary outcome measures. Measurements were recorded before and after treatment.Results. A comparison of pre- and post-treatment test results showed that all dependent variables significantly improved forboth groups (p > 0.001). However, Pilates exercise resulted in greater improvement in terms of balance, spinal curvature, CV angle,and pain (p > 0.001).Conclusions. The Pilates exercise program proved more effective than the traditional physical therapy program in improvingspinal curvature, balance, and function, and in reducing pain in UCS.
Keywords: balance; Pilates exercise; upper cross syndrome; spinal curvature